Роль диагностики в психологической помощи водителям и лицам, перенесшим стрессогенные ситуации на транспорте = The role of psychological diagnosis for assistance drivers and persons who have suffered of stressful the transport situation - E. M. Psiadlo (Kazimierz Wielki University, 2016)
Psiadlo E. M. Роль диагностики в психологической помощи водителям и лицам, перенесшим стрессогенные ситуации на транспорте = The role of psychological diagnosis for assistance drivers and persons who have suffered of stressful the transport situation Journal of Education, Health and Sport. 2016;6(10):566-577. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.179262 http://ojs.ukw.edu.pl/index.php/johs/article/view/4021         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7                                                                                                                                      © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.10.2016.   УДК 612.821   РОЛЬ ДИАГНОСТИКИ В ПСИХОЛОГИЧЕСКОЙ ПОМОЩИ ВОДИТЕЛЯМ И ЛИЦАМ, ПЕРЕНЕСШИМ СТРЕССОГЕННЫЕ СИТУАЦИИ НА ТРАНСПОРТЕ   Э. М. Псядло   Украинский НИИ медицины транспорта МЗ Украины, Одеса, Украина   «Жизнь без стрессов также невозможна, как жизнь, состоящая из одних стрессов, но мы, выбрав второй путь, до сих пор живы»  Афоризм   Реферат Последствия всевозможных стрессогенных ситуаций и дорожно-транспортных происшествий участников, пострадавших и свидетелей могут приводить к шоковому потрясению, острым психотическим и невротическим расстройствам. Автор приводит основную классификацию расстройств, основные тактики психологической помощь пострадавшим. В статье рассматривается схема многоуровневого неврологического и психодиагностического исследования. Приведено ранжирование формализованных методик и тестов на основании психометрических стандартов. Ключевые слова. психодиагностика, стресс, водители, психологическая помощь.   THE ROLE OF PSYCHOLOGICAL DIAGNOSIS for ASSISTANCE Drivers and persons who have suffered of stressful The transport situation   E. M. Psiadlo   Ukrainian Research Institute of Transport Medicine, Odessa, Ukraine   Abstract The effects of various stressful situations and traffic accidents of participants, victims and witnesses may lead to shocks, acute psychotic and neurotic disorders. The author gives the basic classification of disorders, the main tactics of psychological assistance to the victims. The article deals with a multi-level scheme of neurological and psycho-diagnostic research. Powered ranking formalized procedures and tests based on psychometric standards. Keywords. psychodiagnostic, stress, drivers, psychological help.